2022
DOI: 10.1523/jneurosci.0524-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Social Play Behavior Is Critical for the Development of Prefrontal Inhibitory Synapses and Cognitive Flexibility in Rats

Abstract: Sensory driven activity during early life is critical for setting up the proper connectivity of the sensory cortices. We ask here whether social play behavior, a particular form of social interaction that is highly abundant during postweaning development, is equally important for setting up connections in the developing prefrontal cortex (PFC). Young male rats were deprived from social play with peers during the period in life when social play behavior normally peaks [postnatal day 21–42] (SPD rats), followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 75 publications
19
35
0
Order By: Relevance
“…1E and 1J), which suggests that the increase in inhibitory currents reflects the formation of new inhibitory synapses during this period as well as an increase in activity-dependent release. Consistent with our previous findings (Bijlsma et al, 2022), mIPSC frequency was reduced in the mPFC of SPD slices at P85, but the reduction was less pronounced at P42 (Fig. 1I).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1E and 1J), which suggests that the increase in inhibitory currents reflects the formation of new inhibitory synapses during this period as well as an increase in activity-dependent release. Consistent with our previous findings (Bijlsma et al, 2022), mIPSC frequency was reduced in the mPFC of SPD slices at P85, but the reduction was less pronounced at P42 (Fig. 1I).…”
Section: Resultssupporting
confidence: 93%
“…It is therefore likely that a synaptic change in one of the regions will affect the circuit development in the other. Consistent with our previous findings (Bijlsma et al, 2022), we observed that SPD affects the inhibitory, but not the excitatory, connections in both PFC regions. SPD resulted in reduced synaptic inhibition, reminiscent of the impaired development of inhibitory connections that has been described after sensory deprivation (Mowery et al, 2019;Reh et al, 2020).…”
supporting
confidence: 93%
“…Opioids, particularly μ- and κ-receptor agonists, generally inhibit OT and vasopressin (AVP) neuronal firing, thereby suppressing peptide release (Douglas and Russell, 2001; Inenaga et al, 1990; Li et al, 2001; Lutz-Bucher and Koch, 1980; Van de Heijning et al, 1991), likely via presynaptic mechanisms (Clarke and Wright, 1984; Zhao et al, 1988). Interestingly, juvenile play also facilitates the development of inhibitory prefrontal cortex synapses necessary for cognitive and executive function (Bijlsma et al, 2022). This suggests that clinical reports of reduced social behavior and deficits in cognitive performance may be inter-related (Yeoh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…working memory, impulse control, attention, planning and decision making), has been observed in play-deprived animals. Indeed, we have recently demonstrated that deprivation of social play affects the synaptic connectivity in the medial prefrontal cortex (mPFC) of adult rats; we found a reduction in specific inhibitory synaptic inputs onto layer 5 pyramidal cells (Bijlsma et al, 2022, 2023). These findings support the notion that social play behaviour subserves the development of emotional and cognitive capacities and their PFC substrate.…”
Section: Introductionmentioning
confidence: 87%